The relevance of guideline 4.003 (of the S.A. Institute of Chartered Accountants) for financing and dividend policy decisions - Archer, Arminius A.(Arminius Albertus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (D.B.A.) -- University of Stellenbosch, 1980.